Global abnormalities in lymphatic function following systemic therapy in patients with breast cancer. Issue 5 (24th February 2015) - Bains, S. K.; Peters, A. M.; Zammit, C.; Ryan, N.; Ballinger, J.; Glass, D. M.; Allen, S.; Stanton, A. W. B.; Mortimer, P. S.; Purushotham, A. D.
<x xml:space="preserve">Abstract</x> Background Breast cancer‐related lymphoedema (BCRL) is a result of interaction between several pathophysiological processes, and is not simply a 'stopcock' effect resulting from removal of axillary lymph nodes. The aim of this study was to test the hypothesis that there is a constitutional 'global' lymphatic dysfunction in patients who develop BCRL. Methods Lower‐limb lymphoscintigraphy was performed in 30 women who had undergone axillary lymph node dissection at least 3 years previously, of whom 15 had BCRL and 15 did not. No patient had any clinical abnormality of the lower limb. The control group comprised 24 women with no history of cancer or lower‐limb lymphoedema. 99mTc‐Nanocoll was injected subcutaneously into the first webspace of each foot, followed by whole‐body imaging. Scans were reported as abnormal if there was delay in lymph transport or rerouting through skin or deep system. Quantification was expressed as the percentage injected activity accumulating in ilioinguinal nodes. Results Mean(s.d.) ilioinguinal nodal accumulation at 150 min was significantly lower in women with BCRL than in those without (2·7(2·5) versus 5·9(4·8) per cent respectively; P = 0·006). Abnormal findings on lower‐limb lymphoscintigraphy were observed in 17 of the 30 patients: ten of the 15 women who had BCRL and seven of the 15 who did not. None of the 24 control subjects had abnormal scan findings. Conclusion Women with BCRL had reduced lower‐limb lymph drainage, supporting the hypothesis of a predisposition to BCRL. A surprisingly high proportion of patients with breast cancer also demonstrated lymphatic dysfunction, despite clinically normal lower limbs. Possible explanations could be a systemic effect of breast cancer or its treatment, or an unidentified association between breast cancer and lymphatic dysfunction. Registration number: ISRCTN84866416 ( http://www.isrctn.com).